The Effect Of Fiscal Decentralization And Economic Growth On Poverty In Gorontalo Province - Dahlia Destari Inayah Ali; Sri Endang Saleh (Gorontalo State University, 2019)
The implementation of fiscal decentralization policy has a good impact on the development of the potential and creativity of local governments. Effectiveness in managing the results of regional wealth will affect the original income of the region which can then be utilized for the welfare of the community. This study aims to determine the effect of fiscal decentralization and economic growth on poverty in Gorontalo Province. This research uses quantitative methods. The data used in this study were sourced from the Central Statistics Agency and the Directorate General of Fiscal Balance so that the data in this study were secondary data using the econometrics method through a panel data regression equation in the form of a combination of 10-year time series data (2008-2017) and cross section data 6 Regency / City areas in Gorontalo Province. Estimation is done using the Fixed Effect Model (FEM). The results of this study indicate that (1) Partially the degree of fiscal decentralization has a negative effect (unidirectional relationship) and significant on poverty means that the greater the fiscal decentralization variable will have an impact on reducing the level of poverty (2) Partially economic growth has a negative effect (unidirectional relationship) and significant to poverty means increasing economic growth can reduce poverty levels (3) Simultaneously the degree of fiscal decentralization and economic growth have a significant effect on poverty in Gorontalo Province. Keywords: fiscal decentralization, economic growth, poverty